(untitled) (Годишен зборник на Филозофски факултет - Скопје, 2021)
The security policy serves as a key framework for the realization of Spain’s fundamental interests. There is no doubt that security policy has a specific place as it is one of the most important security paradigms that creates the necessary preconditions for progressive development in the security sphere. Undoubtedly, this contributes to shaping Spain’s security measures, in ensuring the necessary political neutrality, and whose action will be within the constitutionally permitted framework. It simultaneously enables the political ideals to grow into a political security doctrine that will strive to produce an optimal concept and strategy of procedures in order to achieve the set goals. Hence, an effective security policy can only succeed if it is based on scientific knowledge. It is a substrate in the shaping of its framework of philosophy and serves as a global basis for the decisive designation of the obligations of all subsystems in society when it comes to specific issues (economic, social, environmental, political, etc.).